The effects of space configuration in pedestrian behavior and the life of public spaces - Guerreiro, M. (2014)
City life conceptualizations becomes a key role in the planning of the cities because it is now realized how people are an important aspect for achieving more lively, safe, sustainable and healthy cities, (Gehl, 2010). Deep understanding of what people need for space is necessary to create urban places where social life can be stimulated. In this paper we will examine space affordances and pedestrian behavior in several plazas of Lisbon city. Through descriptive analyses and quantification it would be discussed how space layout can contribute to the urban life. Moreover, it would be analyzed how the design of the plazas can support not only the formal, but also the informal processes that make a place. The research combines the configuracional analysis with the study of social patterns in order to understand how physical structures influence human behavior. Space Syntax techniques will be used to describe and analyze spatial configurations in relation to social patterns, (Hillier and Hanson, 1984). The model involves a nonmetric understanding of space and suggests that the presence of pedestrian in a network can be explained by topology. At the same time, direct observation of pedestrian behavior was attempted to quantifiably isolate what elements of the space made it effective or, conversely, ineffective (Whyte, 1980). The aim of this paper is to understand the underlying behavior and spatial patterns responsible for the creation of successful public spaces. Exploring the nature of the relationship between spatial patterns, spatial life and social life, the study seeks to find regularities of public embodied space that can be qualified and quantified in an analytical and systematic way. The results suggest how designers and policymakers can manipulate space in order to contribute to the urban life and socialization of the city.